Beautiful boredom idleness and feminine self-realization in the Victorian novel - Maynard, Lee Anna 1973- (McFarland, 2009)
"Boredom in these works is an important means through which female characters are able to achieve a greater sense of self-awareness. The author examines both the deleterious and restorative aspects of boredom and shows how this subtle theme has continued to be used by more modern authors"--Provided by publisher.
"Boredom in these works is an important means through which female characters are able to achieve a greater sense of self-awareness. The author examines both the deleterious and restorative aspects of boredom and shows how this subtle theme has continued to be used by more modern authors"--Provided by publisher.
Includes bibliographical references (p. 183-186) and index
Keywords: James, Henry -- 1843-1916 -- The portrait of a lady; Eliot, George -- 1819-1880 -- Middlemarch; Brontë, Charlotte -- 1816-1855 -- Jane Eyre; Geschichte 1800-1900; English fiction -- 19th century -- History and criticism; Boredom in literature; Self-consciousness (Awareness) in literature; Langeweile -- Motiv